2021
DOI: 10.3390/met11091413
|View full text |Cite
|
Sign up to set email alerts
|

Structural Behavior of Large-Diameter Cylindrical Shell with Stiffened Opening

Abstract: In recent years, there has been a growing demand for renewable energy that is free of power generation by products to address the global climate and resource limitation crises. Wind power generation is maximizing efficiency through constant research and development, and as the use of large capacity turbines increases, the scale of supporting structure also increases. The structural maintenance of hollow towers, the supporting structure of wind turbines, requires the installation of an opening through which wor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…As a crucial engineering structure, the thin-walled steel cylindrical shell has obtained widespread application in most industrial fields. This structure tends to buckle when subjected to axial compression loads, and buckling failure is a critical concern in the design work of thin-walled cylindrical shell structures [1][2][3][4][5][6]. A large number of cylindrical shell buckling experiments have been carried out, and researchers have found that the experimentally observed buckling loads are far short of the theoretical predicted buckling loads of perfect shells [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…As a crucial engineering structure, the thin-walled steel cylindrical shell has obtained widespread application in most industrial fields. This structure tends to buckle when subjected to axial compression loads, and buckling failure is a critical concern in the design work of thin-walled cylindrical shell structures [1][2][3][4][5][6]. A large number of cylindrical shell buckling experiments have been carried out, and researchers have found that the experimentally observed buckling loads are far short of the theoretical predicted buckling loads of perfect shells [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…Foraboschi, P. [7] introduce lateral loads in the analysis, thus providing insight into this loading case. Gusella et al [8] tackle the issue of ductility as an important mechanical property for this analysis with regards to the redistribution of moment loading.…”
Section: Introductionmentioning
confidence: 99%